Designing equitable workplace dietary interventions: perceptions of intervention deliverers - Smith, Sarah A. (BMC Public Health, 2017)
BACKGROUND: Workplaces are a good setting for interventions that aim to support workers in achieving a healthier diet and body weight. However, little is known about the factors that impact on the feasibility and implementation of these interventions, and how these might vary by type of workplace and type of worker. The aim of this study was to explore the views of those involved in commissioning and delivering the Better Health at Work Award, an established and evidence-based workplace health improvement programme. METHODS: One-to-one semi-structured interviews were conducted with 11 individuals in North East England who had some level of responsibility for delivering workplace dietary interventions. Interviews were transcribed verbatim and analysed using thematic framework analysis. RESULTS: A number of factors were felt to promote the feasibility and implementation of interventions. These included interventions that were cost-neutral (to employee and employer), unstructured, involved colleagues for support, took place at lunchtimes, and were well-advertised and communicated via a variety of media. Offering incentives, not necessarily monetary, was perceived to increase recruitment rates. Factors that militate against feasibility and implementation of interventions included worksites that were large in size and remote, working patterns including shifts and working outside of normal working hours that were not conducive to workers being able to access intervention sessions, workplaces without appropriate provision for healthy food on site, and a lack of support from management. CONCLUSIONS: Intervention deliverers perceived that workplace dietary interventions should be equally and easily accessible (in terms of cost and timing of sessions) for all staff, regardless of their job role. Additional effort should be taken to ensure those staff working outside normal working hours, and those working off-site, can easily engage with any intervention, to avoid the risk of intervention-generated inequalities (IGIs). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12889-017-4810-x) contains supplementary material, which is available to authorized users.